Consideration in Microvascular Reconstruction during Times of Social Crises: Perspectives on Resource Utilization - Kent, Sean Lloyd; Kim, Yohanan; Perez, Hector; Frank, Ethan; Gentry, Vance; LaTour, Donn; Inman, Jared (Facial Plastic Surgery, 2020)
Reconstruction of head and neck surgical defects can be a complicated, costly process. While the era of cost-effective medicine has begun to broadly question the necessity of high-cost care, times of extraordinary sociomedical demand bring increased scrutiny to even routine costs and resource utilization. Within this context, we reviewed the advantages, drawbacks, and financial costs of both regional and free flap reconstructions, namely the decreased costs and hospital resource utilization that may be associated with reconstruction using regional flaps. Although beset by reports of partial necrosis in certain regional flaps—particularly the submental island, cervicofacial advancement, and supraclavicular artery island flaps—many reports have demonstrated complication and flap failure rates equivalent to those of free flaps. Additionally, regional flaps have been associated with decreased costs for hospital stay, most notably in cases of postoperative complications. In cases necessitating free flap reconstruction, cost-savings strategies such as bypassing postoperative intensive care unit admissions have been shown to provide satisfactory, safe outcomes. As the head and neck surgeon continues to adapt to the medical pressures of a global pandemic, resource-sparing approaches to oncologic care will persist in their newfound importance.
Keywords: microvascular; free flap; head and neck; pandemic